A non-contact method for rapid alcohol detection
By setting a micro-nano structure layer on the surface of the polydimethylsiloxane film, the light transmittance change caused by alcohol volatility is used to realize a non-contact rapid detection of alcohol, solving the problems of environmental pollution and time-consuming in the prior art, and it is characterized by high efficiency and low cost.
Patent Information
- Application Number
- CN202210613526.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-31
AI Technical Summary
The existing alcohol detection methods have problems of environmental pollution and time-consuming.
By using a non-contact method, by providing a micro-nano structural layer on the surface of the polydimethylsiloxane film, the light transmittance changes are caused by alcohol volatility, so that the presence of alcohol is detected by color changes.
It realizes fast, contactless and energy-consuming alcohol detection, which is simple to operate, low cost, and can accurately detect alcohol in different concentrations.
Smart Images

Figure CN115015234B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alcohol detection, and in particular to a non-contact rapid alcohol detection method. Background Art
[0002] Alcohol is an important chemical reagent with a wide range of applications, but it is flammable and explosive. During use, if a large amount of alcohol leaks, there will be serious safety hazards. Therefore, alcohol detection is very important to ensure the safety of production and life.
[0003] There are many methods for detecting alcohol at present, such as potassium dichromate oxidation spectrophotometry under acidic conditions, electrochemical sensor method and gas chromatography. However, potassium dichromate oxidation spectrophotometry under acidic conditions is easily affected by the environment, has low accuracy, and potassium dichromate has certain pollution to the environment; the electrochemical sensor method has a slow recovery speed and needs to be calibrated and replaced regularly, otherwise the test results will be inaccurate; gas chromatography has high detection sensitivity and fast analysis speed, but the detection cost is relatively high.
[0004] In summary, there are many methods for detecting alcohol at present, but these methods have the disadvantages of environmental pollution and being time-consuming.
[0005] In view of this, it is necessary to propose a non-contact method for rapid alcohol detection to solve the above defects. Summary of the invention
[0006] The main purpose of the present invention is to provide a non-contact method for rapid alcohol detection, aiming to solve the problems of environmental pollution and long time consumption in existing alcohol detection methods. To achieve the above purpose, the present invention provides a non-contact method for rapid alcohol detection, the method comprising the steps of:
[0007] S1, placing a polydimethylsiloxane film on the solution to be tested to obtain an initial color of the polydimethylsiloxane film, wherein the polydimethylsiloxane film comprises a polydimethylsiloxane base and a micro-nano structure layer arranged on the surface of the polydimethylsiloxane base;
[0008] S2, after a preset time has passed, obtaining the current color of the polydimethylsiloxane film;
[0009] S3, comparing the current color of the polydimethylsiloxane film with the initial color of the polydimethylsiloxane film, when the current color is consistent with the initial color, the solution to be tested does not contain alcohol, and when the current color is inconsistent with the initial color, the solution to be tested contains alcohol.
[0010] Preferably, the step S2 specifically includes heating the solution to be tested, and obtaining the current color of the polydimethylsiloxane film after a preset time.
[0011] Preferably, the preset time is 0.1 to 5 minutes.
[0012] Preferably, the distance between the polydimethylsiloxane film and the solution to be tested is 0.1 to 5 cm.
[0013] Preferably, the micro-nanostructure layer of the polydimethylsiloxane film includes a plurality of micro-scale micro-nanostructures, and the size of the micro-nanostructures is 8 to 20 micrometers.
[0014] Preferably, the method for preparing the polydimethylsiloxane film includes: forming a micro-nano structure layer on the surface of the polydimethylsiloxane base by laser processing, and the laser processing method includes: focusing a laser beam on the surface of the polydimethylsiloxane base and processing the micro-nano structure layer by laser direct writing.
[0015] Preferably, the repetition frequency of the laser is 50-200 kHz, the pulse width of the laser is 350 fs, the wavelength of the laser is 1035 nm, the processing speed of the laser is 10-200 mm / s, and the output power of the laser is 1-2 W.
[0016] Compared with the prior art, the non-contact rapid alcohol detection method provided by the present invention has the following beneficial effects:
[0017] The present invention provides a non-contact method for rapid alcohol detection. A micro-nano structure is arranged on the surface of a polydimethylsiloxane film. Alcohol on the surface of the polydimethylsiloxane film can significantly increase or decrease its light transmittance, causing its color to change, so as to detect the presence of alcohol. The method is simple to operate, does not require contact with a solution to be tested, consumes no energy, and is short in time. The preparation of the base material is convenient and quick, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0019] Figure 11 is a scanning electron microscope image of the surface of the polydimethylsiloxane film in one embodiment of the present invention, wherein a is a scanning electron microscope image of the surface of the polydimethylsiloxane substrate before laser processing, and b is a scanning electron microscope image of the surface of the polydimethylsiloxane film with a micro-nano structure layer after laser processing;
[0020] Figure 2 Graphs showing visible light transmittance of the surface of a polydimethylsiloxane film in one embodiment of the present invention, wherein a is a graph showing visible light transmittance of the polydimethylsiloxane film in air after laser processing, and b is a graph showing visible light transmittance of the polydimethylsiloxane film in alcohol after laser processing;
[0021] Figure 3 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 100% alcohol, I is an initial color diagram of the polydimethylsiloxane film, II, III, and IV are color diagrams of the polydimethylsiloxane film after alcohol evaporates for 20s, 48s, and 128s, respectively;
[0022] Figure 4 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 100% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after alcohol evaporates for 77s, 114s, and 198s, respectively;
[0023] Figure 5 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 80% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 60s, 121s, and 202s, respectively;
[0024] Figure 6 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 60% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 61s, 126s, and 205s, respectively;
[0025] Figure 7 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 50% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 63s, 126s, and 214s, respectively;
[0026] Figure 81 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 40% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 86s, 211s, and 293s, respectively;
[0027] Fig. 9 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 30% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 91s, 178s, and 300s, respectively;
[0028] Fig.10 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 20% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol volatilization for 100s, 223s, and 300s, respectively;
[0029] Fig.11 1 is a color change process diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein the test solution is 10% alcohol, a is an initial color diagram of the polydimethylsiloxane film, and b, c, and d are color diagrams of the polydimethylsiloxane film after contact with alcohol for 93s, 203s, and 300s, respectively;
[0030] Fig.12 Schematic diagram of a laser processing device in one embodiment of the present invention.
[0031] Description of Figure Numbers:
[0032] Laser 1; first reflecting mirror 2; second reflecting mirror 3; third reflecting mirror 4; galvanometer 5; processing sample 6; processing platform 7; computer 8.
[0033] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0034] It should be understood that the specific embodiments described herein are only used to explain the present invention, and do not limit the present invention.
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) only explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0037] In addition, the descriptions of "first", "second", etc. in the present invention are only for description purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0038] Please refer to the attached Figures 1 to 12 The present invention provides a non-contact method for rapid alcohol detection, the method comprising the steps of: S1, placing a polydimethylsiloxane film above a solution to be tested, obtaining an initial color of the polydimethylsiloxane film, the polydimethylsiloxane film comprising a polydimethylsiloxane base and a micro-nano structure layer arranged on the surface of the polydimethylsiloxane base;
[0039] S2, after a preset time, obtaining the current color of the polydimethylsiloxane film; S3, comparing the current color of the polydimethylsiloxane film with the initial color of the polydimethylsiloxane film, when the current color is consistent with the initial color, the solution to be tested does not contain alcohol, and when the current color is inconsistent with the initial color, the solution to be tested contains alcohol.
[0040] Specifically, in step S1, a polydimethylsiloxane film is provided, and a micro-nano structure layer is arranged on the surface of the polydimethylsiloxane substrate. The micro-nano structure layer can be arranged in a variety of ways, and can be prepared by laser processing, or by traditional mechanical processing or chemical preparation processes.
[0041] In this embodiment, the method for preparing the polydimethylsiloxane film is to use femtosecond laser processing to prepare a micro-nano structure layer. The laser processing method includes: focusing the laser beam on the surface of the polydimethylsiloxane substrate, and processing the micro-nano structure layer by laser direct writing. The micro-nano structure layer includes multiple micro-scale micro-nano structures, and the size of the micro-nano structure is 8 to 20 microns.
[0042] It should be understood that the specific structure and type of the laser processing device can be set according to actual needs. Fig.12 In this embodiment, a laser processing device is used, including a laser 1, a first reflector 2, a second reflector 3, a third reflector 4, a galvanometer 5, a processing sample 6, a processing platform 7 and a computer 8. The laser 1, the first reflector 2, the second reflector 3, the third reflector 4, the processing platform 7 and the computer 8 are placed in the same plane in sequence, and the galvanometer 5 is located above the processing platform 7. The method of use is that the laser beam first comes out of the laser 1, passes through the first reflector 2, the second reflector 3 and the third reflector 4 successively, enters the galvanometer 5, and finally focuses on the surface of the sample to be processed 6, and the processed graphics (for example, set to a school emblem pattern) and parameters such as energy frequency are drawn and set by the computer 8.
[0043] It should be understood that the laser processing parameters can be adjusted according to actual conditions. In a specific example, laser processing is performed on a polydimethylsiloxane substrate, and the range of laser processing parameters can be selected as follows: repetition frequency of 50 to 200 kHz, pulse width of 350 fs, wavelength of 1035 nm, processing speed of 10 to 200 mm / s, and output power of 1 to 2 W.
[0044] It should be noted that the above parameters are all selected according to the polydimethylsiloxane film characteristics, and the material quality processed by different pulse widths is all different, and the narrower the pulse width, the clearer the edge of the processed object, the smaller the roughness, and the higher the processing accuracy. According to the characteristics of the polydimethylsiloxane base, in the present invention, the pulse width is set to 350fs, and the processing accuracy can be improved. Meanwhile, the wavelength is set to 1035nm, the clarity of the processing accuracy and the processing edge can be improved, and the processing speed is set to 10~200mm / s, the faster the speed, the shorter the processing time of the polydimethylsiloxane film, and the higher the processing efficiency, the output power of the laser is set to 1~2W, and the repetition frequency is set to 50~200kHz. Through these parameters, the polydimethylsiloxane film is processed in coordination with each other, and the polydimethylsiloxane film has super-hydrophobic super-alcoholic characteristics, and this polydimethylsiloxane film can be used to detect the presence of alcohol more accurately.
[0045] Please see attached Figure 1, a is a scanning electron microscope image of the surface of the polydimethylsiloxane film material in an embodiment, wherein the laser processing parameters are: pulse width 350fs, repetition frequency 100KHz, central wavelength 1035nm, output power 2W, scanning spacing 15μm, and processing speed 150mm / s. Before laser processing, the surface of the polydimethylsiloxane base is relatively flat. After laser processing, it can be seen from Figure b that the surface of the polydimethylsiloxane film is processed into a micro-nano structure, and the size of the micro-nano structure is 8-20μm. The micro-nano structure is composed of multiple micro-scale coral-like structures, which have multiple regular and irregular synaptic structures and exhibit super-hydrophobic and super-alcoholic properties.
[0046] In detail, a polydimethylsiloxane film with a micro-nano structure layer is placed above the solution to be tested, and before or just when it is placed, the initial color of the polydimethylsiloxane film is obtained. The initial color is the color of the polydimethylsiloxane film with the micro-nano structure layer under natural light, that is, the color after the micro-nano structure layer is set on the polydimethylsiloxane substrate.
[0047] In this embodiment, the initial color of the polydimethylsiloxane film is generally beige. The distance between the polydimethylsiloxane film and the solution to be tested can be selected according to actual needs. In a preferred choice, the distance between the polydimethylsiloxane film and the solution to be tested can be set to 0.1 to 5 cm.
[0048] It should be noted that in this embodiment, laser processing of polydimethylsiloxane film is adopted, and the initial color of the processed polydimethylsiloxane film is generally beige. Figure 3-11 The color of the polydimethylsiloxane film in the picture is beige, with only differences in shade. Because black and white pictures are required, the pictures have been decolorized.
[0049] It should be noted that before decolorization, it is easier to observe the beige color change process diagram than the black and white color change process diagram in the attached figure, that is, the color change of the polydimethylsiloxane film can be more obviously observed under actual conditions.
[0050] Specifically, in step S2, after a preset time has passed, the color of the polydimethylsiloxane film is obtained again, which is the current color. The preset time can be set according to actual needs. In a preferred choice, the preset time can be set to 0.1 to 5 minutes.
[0051] It is worth noting that in step S3, after obtaining the current color of the polydimethylsiloxane film, the current color of the polydimethylsiloxane film is compared with the initial color of the polydimethylsiloxane film to determine whether the current color has changed compared to the initial color. When the current color is consistent with the initial color, it means that the solution to be tested does not contain alcohol. When the current color is inconsistent with the initial color, that is, when the current color is lighter or darker than the initial color, it means that the solution to be tested contains alcohol.
[0052] The detection principle is: when alcohol evaporates onto the polydimethylsiloxane film, it will change its light transmittance, significantly increase or decrease its light transmittance, causing the color of the polydimethylsiloxane film to change, becoming darker or lighter. For example, in this embodiment, the color of the polydimethylsiloxane film will become lighter. Under certain conditions, the color of the polydimethylsiloxane film will become darker, so the color change can be used to determine whether the solution to be tested contains alcohol and detect the presence of alcohol in the solution to be tested.
[0053] Specifically, the above specific embodiments are still used for explanation. Figure 2 The processed polydimethylsiloxane film was placed in the air, and the light transmittance at a wavelength of 800nm was measured to be 54.43%; the polydimethylsiloxane film was placed in 100% alcohol, and the light transmittance at a wavelength of 800nm was measured to be 82.01%. The change in light transmittance can be clearly seen.
[0054] In addition, when the polydimethylsiloxane film was placed in 80% alcohol, the transmittance at a wavelength of 800nm was measured to be 73.86%; when the polydimethylsiloxane film was placed in 60% alcohol, the transmittance at a wavelength of 800nm was measured to be 71.24%; when the polydimethylsiloxane film was placed in 50% alcohol, the transmittance at a wavelength of 800nm was measured to be 65.22%.
[0055] It can be further explained that the light transmittance of the polydimethylsiloxane film will change at different alcohol concentrations. Therefore, when alcohol evaporates onto the polydimethylsiloxane film, the light transmittance of the polydimethylsiloxane film will change, and the color of the polydimethylsiloxane film will also change accordingly. Therefore, the polydimethylsiloxane film can detect the presence of alcohol more accurately.
[0056] It should be understood that heating the test solution can accelerate the volatilization of alcohol and more quickly detect whether the test solution contains alcohol. The heating temperature can be selected according to actual needs.
[0057] Specifically, still using the above specific embodiment as an example, a polydimethylsiloxane film with a micro-nano structure layer is processed by laser, wherein the laser processing parameters are: pulse width of 350fs, pulse repetition frequency of 100KHz, central wavelength of 1035nm, output power of 2W, scanning spacing of 15μm, and processing speed of 150mm / s. To obtain its initial color, select a container, add 100% alcohol into it, the distance between the alcohol solution and the bottle mouth of the container is 0.3 cm, place the polydimethylsiloxane film on the bottle mouth of the container, and heat the container in a water bath, and the heating temperature is set to 40 degrees. Please refer to the attached Figure 3 , Figure II is the color image of the polydimethylsiloxane film after waiting for 20 seconds, III is the color image after waiting for 48 seconds, and IV is the color image after waiting for 128 seconds.
[0058] It can be seen that after waiting for 20 seconds, the polydimethylsiloxane film has undergone an obvious color change. The detection time is short, and the longer the time, the more obvious the change. The presence of alcohol can be accurately detected. The method is simple to operate, does not require contact with the solution to be tested, has low cost, no energy consumption, and is short in time.
[0059] The present invention also provides application of a polydimethylsiloxane film in detecting alcohol. The polydimethylsiloxane film comprises a polydimethylsiloxane base and a micro-nano structure layer arranged on the surface of the polydimethylsiloxane base.
[0060] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0061] Example 1
[0062] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0063] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 100% in a container, placing the polydimethylsiloxane film at the mouth of the container, and the distance between the polydimethylsiloxane film and the alcohol solution is 1 cm.
[0064] (3) After 77s, 114s, and 198s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0065] like Figure 4 As shown, Figure 4 Figure a is a color change process diagram of the polydimethylsiloxane film during the evaporation of 100% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 77s, 114s, and 198s, respectively. All of them are optical pictures. It can be seen from the figures that the longer the alcohol evaporates, the lighter the color of the polydimethylsiloxane film.
[0066] Example 2
[0067] (1) providing a polydimethylsiloxane substrate, and using a laser processing method to process a micro-nano structure layer on the surface of the polydimethylsiloxane substrate by laser direct writing; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s;
[0068] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 80% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0069] (3) After 60s, 121s, and 202s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol. Figure 5 As shown, Figure 5 Figure a is a diagram showing the color change of the polydimethylsiloxane film during the evaporation of 80% alcohol. Figures b, c, and d are the color change diagrams after the alcohol solution evaporates for 60s, 121s, and 202s, respectively. All of them are optical pictures. It can be seen from the figures that the longer the alcohol evaporates, the lighter the color of the polydimethylsiloxane film.
[0070] Example 3
[0071] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0072] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 60% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0073] (3) After 61s, 126s, and 205s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0074] like Figure 6 As shown, Figure 6 Figure a is a diagram showing the color change of the polydimethylsiloxane film during the evaporation of 60% alcohol. Figures b, c, and d are the color change diagrams after the alcohol solution evaporates for 61s, 126s, and 205s, respectively. All of them are optical images. It can be seen from the figures that the longer the alcohol evaporates, the lighter the color of the polydimethylsiloxane film.
[0075] Example 4
[0076] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0077] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 50% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0078] (3) After 63 seconds, 126 seconds, and 214 seconds respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0079] like Figure 7 As shown, Figure 7 Figure a is a color change process diagram of the polydimethylsiloxane film during the evaporation of 50% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 63s, 126s, and 214s, respectively. All of them are optical pictures. It can be seen from the figures that the longer the alcohol evaporates, the lighter the color of the polydimethylsiloxane film.
[0080] Example 5
[0081] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0082] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 40% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0083] (3) After 86 s, 211 s, and 293 s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0084] like Figure 8 As shown, Figure 8 Figure a is a color change process diagram of the polydimethylsiloxane film during the volatilization of 40% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 86s, 211s, and 293s, respectively. All of them are optical pictures. It can be seen from the figures that after a period of time, the color of the polydimethylsiloxane film is lighter than the initial color, indicating that even when the alcohol concentration is not high, the presence of alcohol can still be clearly detected.
[0085] Example 6
[0086] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0087] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 30% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0088] (3) After 91 s, 178 s, and 300 s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0089] like Fig. 9 As shown, Fig. 9 Figure a is a color change process diagram of the polydimethylsiloxane film during the volatilization of 30% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 91s, 178s, and 300s, respectively. All of them are optical pictures. It can be seen from the figures that after a period of time, the color of the polydimethylsiloxane film is lighter than the initial color, indicating that even when the alcohol concentration is not high, the presence of alcohol can still be clearly detected.
[0090] Example 7
[0091] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0092] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 20% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0093] (3) After 100 s, 223 s, and 300 s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0094] like Fig.10 As shown, Fig.10 Figure a is a color change process diagram of the polydimethylsiloxane film during the volatilization of 20% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 100s, 223s, and 300s, respectively. All of them are optical pictures. It can be seen from the figures that after a period of time, the color of the polydimethylsiloxane film is lighter than the initial color, indicating that even when the alcohol concentration is not high, the presence of alcohol can still be clearly detected.
[0095] Example 8
[0096] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0097] (2) Obtaining the initial color of the polydimethylsiloxane film; placing alcohol with a concentration of 10% in a container, and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0098] (3) After 93 s, 203 s, and 300 s, respectively, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is lighter than the initial color, which means that the polydimethylsiloxane film can detect the presence of alcohol.
[0099] like Fig.11 As shown, Fig.11 Figure a is a color change process diagram of the polydimethylsiloxane film during the volatilization of 10% alcohol. Figures b, c, and d are color change diagrams after the alcohol solution evaporates for 77s, 114s, and 198s, respectively. All of them are optical images. It can be seen from the figures that after a period of time, the color of the polydimethylsiloxane film is lighter than the initial color, indicating that even when the alcohol concentration is not high, the presence of alcohol can still be clearly detected.
[0100] Example 9
[0101] (1) A polydimethylsiloxane substrate is provided, and a micro-nano structure layer is processed on the surface of the polydimethylsiloxane substrate by laser direct writing using a laser processing method; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 100 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 15 μm, and processing speed of 150 mm / s.
[0102] (2) Obtaining the initial color of the polydimethylsiloxane film; placing the aqueous solution in a container and placing the polydimethylsiloxane film at the mouth of the container, with the distance between the polydimethylsiloxane film and the alcohol solution being 1 cm.
[0103] (3) After 300 seconds, the current color of the polydimethylsiloxane film is obtained and compared with the initial color. The current color is consistent with the initial color, that is, when the test solution is an aqueous solution and does not contain alcohol, the color of the polydimethylsiloxane film will not change.
[0104] Since the processed polydimethylsiloxane film has super-hydrophobic properties, the aqueous solution will not spread on its surface, will not change its light transmittance, and will not produce color changes.
[0105] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A non-contact method for rapid alcohol detection, characterized in that: The method comprises the steps of: S1, placing a polydimethylsiloxane film on the solution to be tested to obtain an initial color of the polydimethylsiloxane film, wherein the polydimethylsiloxane film comprises a polydimethylsiloxane base and a micro-nano structure layer arranged on the surface of the polydimethylsiloxane base; The micro-nano structure layer of the polydimethylsiloxane film comprises a plurality of micro-scale micro-nano structures, and the size of the micro-nano structures is 8 to 20 microns; The preparation method of the polydimethylsiloxane film comprises: forming a micro-nano structure layer on the surface of the polydimethylsiloxane substrate by laser processing, wherein the laser processing comprises: focusing a laser beam on the surface of the polydimethylsiloxane substrate and processing the micro-nano structure layer by laser direct writing; The repetition frequency of the laser is 50-200kHz, the pulse width of the laser is 350fs, the wavelength of the laser is 1035nm, the processing speed of the laser is 10-200mm / s, and the output power of the laser is 1-2W; S2, after a preset time has passed, obtaining the current color of the polydimethylsiloxane film; S3, comparing the current color of the polydimethylsiloxane film with the initial color of the polydimethylsiloxane film, when the current color is consistent with the initial color, the solution to be tested does not contain alcohol, and when the current color is inconsistent with the initial color, the solution to be tested contains alcohol.
2. The method for non-contact rapid alcohol detection according to claim 1, characterized in that: The step S2 specifically includes heating the solution to be tested, and obtaining the current color of the polydimethylsiloxane film after a preset time.
3. The method for non-contact rapid alcohol detection according to claim 1, characterized in that: The preset time is 0.1 to 5 minutes.
4. The non-contact rapid alcohol detection method according to claim 1, characterized in that: The distance between the polydimethylsiloxane film and the solution to be tested is 0.1 to 5 cm.
Citation Information
Patent Citations
Manufacturing method for polydimethylsiloxane microfilm biosensor based on surface stress
CN102502478A
Contactless type breathalyzer
KR102219408B1